Parametric Geometrical Study of OOO-Microstrip Circuit with Dual-Band Bandpass NGD Behavior - Yang, Rong; Wan, Fayu; Nebhen, Jamel; Lallechere, Sebastien; Ravelo, Blaise (Společnost pro radioelektronické inženýrství, 2021)
This paper introduces a bandpass (BP) NGD circuit design engineering. The developed circuit is de¬signed and implemented using distributed microstrip tech-nology and operates with outstanding dual-band bandpass NGD performance added with low attenuation. The BP NGD topology presents an innovative geometrical shape represented by an OOO (triple O) structure composed of multi-parameter parallel transmission lines (TLs) based elements. The OOO type NGD circuit is mainly composed of different physical length TLs and two identical coupled lines (CLs). Then extensive parameter NGD analyses are elaborated to investigate on the influences of each physical size of OOO circuit on the NGD performances. Through the difference of physical length of transmission line, the delay can be adjusted. Through the results of simulation and measurement, it can be seen that the center frequency points are about 0.75 GHz and 1.46 GHz respectively, and the time delay is about –1.83 ns and –2.6 ns respectively.
Keywords: Negative group delay (NGD); bandpass NGD function; dual-band frequency; OOO-microstrip circuit; parametric analyses